Rheological properties of different degree of pregelatinized rice flour batter - Rohaya, M.S.; Maskat, M.Y.; Ma'aruf, A.G. (Universiti Kebangsaan Malaysia, 2013)
The effect of using rice flour at different degree of gelatinization on rheological properties of a batter system was studied. Rice flour was gelatinized by heated for 20, 40, 60 and 90 min. The treated rice flour was used to prepare batters by stirring it for 2 min. The batter were subjected to determination of apparent viscosity, consistency and flow behavior index and storage modulus G’. The results showed that degree of gelatinization, DG of rice flour increased with the increased heating period up to 60 min. All rice flour batter shown shear thinning behavior since the viscosity decreased with increasing shear rate. The behavior was proven by the value of consistency coefficient, K more than 0 and flow behavior index, n less than 1. Rice flour batter heated in a longer period has higher viscosity and could be attributed by lower water content. The storage modulus, G’ of heated rice flour were lower than G’ of commercial and unheated rice flour. This result was probably because of the lower amylose and protein content in the modified starch pastes.